Remittance from Gurkha’s as a Source of Foreign Currencies and Contribution to Livelihood Practices of Left Behind - Thapa, Laxmi (Journal of Development Review, 2020)
Study shows that remittances from the Gurkha’s are an important source of foreign currency for Nepal which has also been contributing as a reliable source of income for the family and relatives left behind. The article depicts the statistical data of Gurkhas who have been in service and retired, in the Indian army and the British army. For the study here, I have deployed the observation and purposive sampling method followed by semi-structured interview techniques to collect the required data. My respondents are the household heads of employees and office personnel of Indian and British pension camp for primary data, and records from respective camp for secondary data. The finding shows a huge amount of Indian rupees and British pound as a foreign currency remitted by Gurkhas. The data shows that there are NPR.1,28,52 crores inward remittance come to Nepal annually from Gurkhas. On top of that, the remittances are playing a vital role to uplift the economic condition of left behind. However, the absence of energetic migrants has changed the traditional socio-cultural construction of the community, the role of women in the household chore, and demographic composition. Positively, women are empowered and economically they get a reliable source of income throughout their life. While single parenting, the loneliness of old parents, and sacrifice for social relations seem very challenging to manage them as a social being. Findings also show that there is a tangible gap between the pace of global economic advancement and local economic advancement, which has encouraged youths to join the army.